Importance of Compost, Bentonite, and Calcium Oxide in Reducing Trace Element Content in Maize on Agricultural Soil Contaminated with Diesel Oil - Mirosław Wyszkowski; Natalia Kordala (Agriculture, 2023)
Soil contaminated with petroleum substances is classified as hazardous, i.e., particularly harmful to the proper functioning of environmental ecosystems. It is therefore necessary to take measures to restore the homeostasis and ecological potential of degraded areas. The study aim was to determine the impact of bentonite, compost, and calcium oxide (CaO) on trace element content in the maize grown on diesel oil (DO)-contaminated soil. Increasing doses of the petroleum substance increased the accumulation of chromium (Cr), lead (Pb), copper (Cu), nickel (Ni), manganese (Mn), cobalt (Co), and cadmium (Cd) in maize. The largest increases were found for Cu (by 76%), Co (by 73%), and Pb (by 42%). All soil amendments proved useful for in situ stabilization of anthropogenically transformed soils. Bentonite reduced Cr (by 94%), Cu (by 84%), and Mn content (by 53%), while compost reduced the contents of Cu (by 75%), Mn (by 44%), and iron (Fe—by 29%) in maize. CaO significantly reduced the levels of Cr (by 94%), Cu (by 84%), Ni (by 66%), Mn (by 32%), Co (by 72%), zinc (Zn—by 30%), and Cd (by 22%) in maize. The effects of compost and bentonite on maize chemical composition were smaller than that achieved with CaO, and the direction of changes in elements content depended on the DO dose and the element type.